Gestión y demanda turística en la Parroquia de Huigra Cantón Alausí, Provincia de Chimborazo. - Calle Castro, Ibeth Nathaly (2019)
The main objective is to evaluate the management of the Autonomous Decentralized Parish Government and its influence on the tourist demand in the parish of Huigra, Cantón Alausí, Province of Chimborazo. The following research is exploratory, descriptive and correlational, the design of the study is not experimental and is composed of two phases: Phase 1. - The sample is not probabilistic, it was selected with a specific purpose such as the application of interviews with tourism managers. as: authorities, technicians and tourism operators of the Huigra parish; Phase 2.- The sample is probabilistic, it was taken in a random way, that is to say, 191 tourists who visit the parish of Huigra over 14 years old had the possibility of being selected for the research. As a result of the interviews, it was evident that the parish has the necessary physical and human inputs to achieve potential tourism development, through surveys it was detected that there is no adequate promotion of tourist attractions and activities that has Huigra, therefore 100% of the surveyed tourists are of Ecuadorian nationality, for that reason it allowed us to verify the historical, natural and cultural wealth that it possesses, but unfortunately the risk of deterioration is being run due to the lack of concern on the part of authorities and inhabitants, given that they do not view tourism as an economic source. When carrying out the hypothesis testing, it was shown that, if tourism management has a significant influence on tourism demand, finally a proposal was proposed to help formulate strategies to cover the needs of the parish.